El cos, el sexe i la dona en el «Recull d'Eximplis» - Ysern i Lagarda, Josep A. (Caplletra. Revista Internacional de Filologia, 2015)
The collection of exempta edited by Marià Aguiló in 1881, samples materials related to all kinds of subjects, not excluding some –like those explored in this article– of an humorous or rather misogynous nature, related to sexual behaviour, where women are presented as a mischivious source of moral danger.